Isolation by IMS Procedure and Molecular Characterisation of Escherichia Coli O157:B7 - Alias, Rozila (1999)
Escherichia coli O157:H7 was discovered in association with the outbreak of hemorrhagic colitis, hemolytic uremic syndrome and thrombotic thrombocytopenic purpura in 1982. Since then, this organism has become a very important cause of foodbome infection in the developed countries. The Immunomagnetic Bead Separation (IMS) and QUIX™ strip test 0157 techniques were used to detect E. coli O157:H7 in the 40 samples of frozen beef. Twenty nine out of 40 samples of frozen beef (72.5%) were presumptive positive with the strip QUIX O157 strip. 18 of the 29 presumptive positive samples were confirmed positive by using immunomagnetic bead separation (IMS) and conventional methods. A total of 123 isolates from the 18 positive samples were further characterised using plasmid, antibiotic profiling and randomly amplified polymorphic DNA (RAPD). All the strains (100010) were resistant to bacitracin, cephalothin and penicillin. Others, 85.4, 81.3, 70.0, 47.2, 41.5, 32.5, 27.6, 23.6 and 12.2% were resistant to carbenicillin, erythromycin, streptomycin, kanamycin, nalidixic acid, tetracycline, chloramphenicol, ampicillin and gentamycin, respectively. The multiple antibiotic resistance index (MAR) for E. coli O157:H7 isolates ranged between 0.38 to 0.92. 123 isolates were grouped into sixty six resistotypes with resistance to five or more antibiotics. 97.3% of E. coli O157:H7 strains contained plasmid DNA ranging in size from 1.34 MDa to 60 MDa. Based on the plasmid size, the strains could be grouped into 5 groups or profiles; profile I contained 60 MDa and 2.5 MDa (49.6%); profile IT, 60 MDa (43.1%), profile III and IV, 60 MDa and small plasmids and profile 0 represented plasmidless strains. A 60 MDa plasmid which has been identified as a serotype specific for E. coli O157:H7 was detected in all the 123 strains. Ten primers were screened but only three primers, Gen1-50-02, Gen1-50-09 and Gen1-50-10 were chosen for PCR reactions because they gave reproducibility PCR products with one, five and six RAPD patterns respectively. These amplified fragments ranged from 0.25 to 4.0 kb in sizes.